HUBUNGAN TINGKAT KECEMASAN TERHADAP KUALITAS TIDUR PADA IBU HAMIL TRIMESTER III DI DESA PARAKANTUGU KECAMATAN CIJATI KABUPATEN CIANJUR TAHUN 2024 - Sapariah, Astri; Novianti, Risha (Yayasan Putra Sukamanah Sejahtera, 2026)
Pregnancy is a condition in which a woman carries a developing fetus in her body. Pregnancy is divided into three trimesters: the first trimester (0–12 weeks), the second trimester (13–27 weeks), and the third trimester (28–40 weeks). During the third trimester, pregnant women tend to experience disturbances in sleep quality caused by several factors, such as anxiety about their condition and physiological changes. These physiological changes include pressure on the urinary bladder by the enlarged abdomen, causing more frequent urination, pressure on the diaphragm, and increased oxygen demand, which results in shorter breathing. A decline in sleep quality can also have negative impacts on the health of both the mother and the fetus. One of the consequences is disrupted metabolism, which makes the mother feel easily fatigued and may affect the preparation process for childbirth. Objective: This study aimed to determine whether there is a relationship between anxiety levels and sleep quality among third-trimester pregnant women. Methods: This study used a quantitative research method with a cross-sectional approach. The population consisted of 76 respondents, and total sampling technique was applied. Results: The findings showed that anxiety levels among respondents were categorized as mild (43.4%), moderate (38.2%), severe (17.1%), and very severe (1.3%). The results also indicated that 63.2% of third-trimester pregnant women experienced poor sleep quality. Based on the statistical analysis using the Chi-square test, a p-value of 0.001 < 0.05 was obtained, indicating a significant relationship between the two variables. Conclusion: It can be concluded that there is a significant relationship between anxiety levels and sleep quality among third-trimester pregnant women.